Model synergy of tahfiz Alquran programs in Wadi Mubarak Islamic Boarding School, Bogor - Haris, Abdul Rauf (Ta’dibuna: Jurnal Pendidikan Islam, 2023)
The high interest in the Qur’an tahfizh program encourages many pesantren to further develop their management models. This paper aims to examine how Wadi Mubarak Islamic Boarding School synergizes the Qur’an memorization program through different types and levels of education it manages. This research applies a descriptive qualitative method using several data collection techniques including literature and documentation studies, in-depth interviews, and involved observations. This study found six forms of synergy in the management of the Quran tahfizh program. First, the alignment of vision and mission in each program, which is aimed at strengthening the Quran tahfizh program. Second, establishing different Quran memorization programs with different segments of students. Third, the establishment of the same competency standards for graduates in the field of 30 juz Quran memorization. Fourth, the absorption and distribution program of graduates to meet the needs of human resources in each pesantren’s Quran memorization program. Fifth, the establishment of a road map and development goals. Sixth, the management of special non-educational programs that still aim to support the implementation of the Qur’an tahfizh program. Abstrak Tingginya animo terhadap program tahfizh Alquran mendorong banyak pesantren untuk terus mengembangkan model manajemennya. Tulisan ini bermaksud untuk mengkaji bagaimana Pondok Pesantren Wadi Mubarak melakukan sinergi program tahfizh Alquran melalui berbagai jenis dan jenjang pendidikan yang dikelolanya. Penelitian ini menerapkan metode deskriptif kualitatif menggunakan beberapa teknik pengumpulan data mencakup studi pustaka dan dokumentasi, wawancara mendalam dan pengamatan terlibat. Penelitian ini menemukan enam bentuk sinergi yang dalam pengelolaan program tahfizh Alquran. Pertama, penyelarasan visi dan misi di setiap program yang berorientasi pada penguatan program tahfizh Alquran. Kedua, mendirikan berbagai program tahfizh Alquran dengan segmen peserta didik yang beragam. Ketiga, menetapkan standar kompetensi lulusan yang sama di bidang tahfizh Alquran 30 juz. Keempat, program penyerapan dan distribusi lulusan untuk memenuhi kebutuhan sumber daya manusia di setiap program tahfizh Alquran miliki pesantren. Kelima, penetapan peta jalan dan target pengembangan. Keenam, pengelolaan program khusus non-pendidikan yang tetap bertujuan untuk mendukung penyelenggaraan program tahfizh Alquran.